Early Life Abuse Moderates the Effects of Intranasal Oxytocin on Symptoms of Premenstrual Dysphoric Disorder: Preliminary Evidence From a Placebo-Controlled Trial - Walsh, Erin C.; Eisenlohr-Moul, Tory A.; Pedersen, Cort A.; Rubinow, David R.; Girdler, Susan S.; Dichter, Gabriel S. (Frontiers in Psychiatry, 2018)
Background: Although intranasal oxytocin (OXT) has been proposed to be a promising treatment for some psychiatric disorders, little research has addressed individual difference factors that may predict response to OXT. One such factor is early life abuse (ELA), which has widespread influences on social-emotional processing and behavior. This single-blind, placebo-controlled crossover trial examined the role of ELA in shaping the effects of intranasal OXT (vs. placebo) on daily behavioral symptoms in women with three or more prospectively-diagnosed cycling symptoms of premenstrual dysphoric disorder (PMDD). Methods: Participants were ten women with PMDD (n=8) or subthreshold PMDD (n=2), who had experienced ELA prior to age 13 (n=5) or no ELA (n=5). They completed two study visits during the late luteal (premenstrual) phase: once following administration of intranasal OXT and once following intranasal placebo (counterbalanced). Participants then self-administered OXT or placebo at home three times per day for five days or until menstrual onset, and prospectively rated daily emotional symptoms of PMDD. Power was adequate to detect medium main and interactive effects. Results: Among women with ELA, intranasal OXT (vs. placebo) increased the premenstrual emotional symptoms of PMDD, whereas among women without ELA, OXT decreased symptoms. Conclusion: This study adds to a growing literature highlighting the importance of considering historical social contexts and traits (such as ELA) as moderators of therapeutic response to OXT.